(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2014)
Clinical judgment, and the view of the prebriefing background of those members accepting organized prebriefing and those getting customary prebriefing exercises, were looked at. The connection between simulation performance and students’ self-evaluated prebriefing background was likewise inspected. Scores from the Creighton Competency Assessment Instrument and the Prebriefing Background Scale were investigated utilizing parametric and non-parametric statistics. A factually noteworthy contrast was shown between bunches for competency performance (p